Development of Floating-Mucoadhesive Microsphere for Site Specific Release of Metronidazole - Md. Lutful Amin; Tajnin Ahmed; Md. Abdul Mannan (Tabriz University of Medical Sciences, 2016)
Purpose: The purpose of this study was to develop and evaluate metronidazole loadedfloating-mucoadhesive microsphere for sustained drug release at the gastric mucosa.Methods: Alginate gastroretentive microspheres containing metronidazole were preparedby ionic gelation method using sodium bicarbonate as gas forming agent, guar gum asmucoadhesive polymer, and Eudragit L100 as drug release modifier. Carbopol was used forincreasing the bead strength. The microspheres were characterized by scanning electronmicroscopy and evaluated by means of drug entrapment efficiency, in vitro buoyancy, andswelling studies. In vitro mucoadhesion and drug release studies were carried out in order toevaluate site specific sustained drug release.Results: All formulations showed 100% buoyancy in vitro for a prolonged period of time.Amount of guar gum influenced the properties of different formulations. The formulationcontaining drug and guar gum at a ratio of 1:0.5 showed the best results with 76.3% drugentrapment efficiency, 61.21% mucoadhesion, and sustained drug release. Carbopol wasfound to increase surface smoothness of the microspheres.Conclusion: Metronidazole mucoadhesive-floating microspheres can be effectively usedfor sustained drug release to the gastric mucosa in treatment of upper GIT infection.